The Philippine bureaucracy: prospects for administrative reform and indigenization - Peñalosa, Ma. Carmen V. (2014)
The prevailing view concerning administrative reform as the simple replacement of "traditional patrimonial systems" by "modern administrative systems" is examined in this article in the context of Philippine history and the indigenization movements in the Philippine Social Sciences with particular reference to Pantayong Pananaw, Sikolohiyang Pilipino and Pilipinolohiya as these found resonance in the field of Public Administration. The objective of the article is to review the literature on Philippine bureaucracy in order to put administrative reform agenda in the context of Filipino society, culture and history, and thus, finally possibly improve the long term prospects for reforming the Philippine bureaucracy.
Keywords: Bureaucracy -- Philippines